The Influence of Product, Personalization and Community Factors in the E-Marketing Mix on Erigo Fashion Customer Satisfaction in Indonesia - Boyke, Silvanus; Aloysius Hari Kristianto (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research is motivated by the rapid growth of online business in Indonesia. Because of this, business people realize that more and more people tend to choose to shop online rather than offline. The aim of this research is to determine the impact of product, personalization and community in the e-marketing mix on customer satisfaction for Erigo fashion products in Indonesia. The e-marketing mix components that are the focus of this research were developed based on the model proposed by Kalyanam & McIntyre (2002), focusing on 3 components, namely product, personalization and community. This research is confirmatory research that uses a quantitative approach with survey methods (field studies). The population that is the subject of the research is all consumers in Indonesia who have purchased Erigo products online at least once. Sampling used a non-probability sampling method with purposive sampling technique, where the number of respondents who participated in filling out this questionnaire was 250 people. Data analysis was carried out using multiple linear regression, for data processing using IBM SPSS Statistics 26 software. The research results showed that product, personalization and community variables had a significant effect on customer satisfaction for Erigo fashion products in Indonesia.